Nylon blend pipe compositions resistant to slow crack growth and methods of making the same
Patent Information
- Application Number
- CN202611455915.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-18
- Publication Date
- 2026-10-23
AI Technical Summary
[0004]本发明针对现有技术中化学再生PA6管材抗慢速裂纹增长性能不足、与PA66相容性差的技术问题,提供一种抗慢速裂纹增长的尼龙共混管材组合物及其制备方法
[0036](1)本发明通过特定端基含量的再生PA6与PA66共混,并在端环氧基超支化聚酯的增容/微交联、纳米晶须的取向增强、稀土硬脂酸盐的协同稳定、管材成型过程中的对熔体拉伸比和冷却速率的控制等多重机制作用下,显著提升了该管材制品的SCG抵抗能力。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer material processing and recycling technology, specifically relating to a nylon blend pipe composition resistant to slow crack growth and its preparation method. Background Technology
[0002] Polyamide (PA, nylon) pipes are widely used in automobiles, electronics, and pipelines due to their excellent mechanical properties, heat resistance, and chemical resistance. PA6 and PA66 are the two most widely used nylon materials. However, virgin nylon resin is expensive, and waste nylon products put pressure on the environment. Therefore, using chemical recycling methods to prepare recycled PA6 and reuse it in pipe manufacturing has significant economic and environmental implications. Compared to physically and mechanically recycled PA6, chemically recycled PA6 has a more regular molecular chain structure, lower impurity content, and properties closer to virgin resin. However, the recycling process inevitably leads to a wider molecular weight distribution and changes in the content of end groups (amino and carboxyl groups), which affects its crystallization behavior and processing stability, especially significantly reducing the material's resistance to slow crack growth (SCG). Slow crack growth is the main form of brittle failure in plastic pressure pipes under long-term hydrostatic stress and is a core indicator for measuring pipe service life and safety.
[0003] In existing technologies, improving the performance of chemically recycled PA6 products typically involves blending with PA66, adding elastomer toughening agents, or introducing nucleating agents. For example, CN113637193A discloses a nylon insulating strip or a reinforced nylon / glass fiber reinforced PA6 / PA66 composite material. By adding glass fiber, toughening agents, and nucleating agents, the creep properties, wear resistance, oxidation resistance, and light resistance of the composite material are improved. Its main focus is on enhancing mechanical strength (tensile and bending), heat distortion temperature, and flame retardant properties, but it does not address resistance to environmental stress cracking (SCG). Furthermore, due to fluctuations in end-group content, recycled PA6 exhibits poor interfacial compatibility with PA66 and inorganic fillers. Direct blending easily leads to phase separation, reducing the long-term performance of the pipe products. Therefore, how to address the characteristics of chemically recycled PA6 through formulation design and process control, while maintaining excellent mechanical and processing properties, synergistically improving the pipe's resistance to slow crack growth, is a pressing technical challenge that needs to be solved. Summary of the Invention
[0004] This invention addresses the technical problems of insufficient resistance to slow crack growth and poor compatibility with PA66 in existing chemically regenerated PA6 pipes by providing a nylon blend pipe composition resistant to slow crack growth and its preparation method.
[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution:
[0006] In a first aspect, the present invention provides a nylon blend tubing composition resistant to slow crack growth, comprising the following components in parts by weight:
[0007] Chemically regenerated PA6 40-70 parts
[0008] PA66 10-30 servings
[0009] 0.5–5 parts of terminal epoxy-terminated hyperbranched polyester
[0010] 0.1–3 parts of nanocrystal nucleating agent
[0011] Rare earth metal stearates, 0.05–0.3 parts
[0012] Antioxidant 0.1 to 1 part
[0013] Lubricant 0.1 to 1 part.
[0014] In this invention, the chemically regenerated PA6 is a regenerated PA6 prepared through depolymerization and repolymerization or dissolution and reprecipitation processes. These processes are well-known chemical recycling methods in the art, the core of which lies in depolymerizing waste PA6 into the monomer caprolactam and then repolymerizing it, or dissolving it and precipitating it through non-solvent precipitation, thereby effectively removing impurities and restoring the molecular chain structure.
[0015] To achieve the anti-SCG properties of this invention, the end-group content and viscosity range of the chemically recycled PA6 must be strictly controlled. Specifically, in a 96% concentrated sulfuric acid solution with a sample concentration of 0.5 g / dL, under test conditions of 25°C, the relative viscosity is 2.4–3.0, the end-amino group content is 30–60 mmol / kg, and the end-carboxyl group content is 40–80 mmol / kg. Chemically recycled PA6 within this range exhibits moderate molecular chain activity, enabling efficient chain extension / branching reactions with terminal epoxy hyperbranched polyesters while avoiding excessive crosslinking, thus ensuring the basic mechanical framework of the matrix resin.
[0016] As a preferred embodiment, an exemplary preparation method for the chemically regenerated PA6 is as follows: Waste PA6 products are depolymerized in caprolactam monomer at 220–260°C. The purified caprolactam monomer is obtained through distillation and crystallization. Then, the monomer is subjected to ring-opening polymerization at 250–270°C under nitrogen protection for 4–8 hours in the presence of a ring-opening catalyst (such as aminocaproic acid). After granulation, extraction, and drying, chemically regenerated PA6 is obtained. By adjusting the polymerization time and post-treatment conditions, the relative viscosity of the product can be controlled within the range of 2.4–3.0, the terminal amino group content within 30–60 mmol / kg, and the terminal carboxyl group content within 40–80 mmol / kg.
[0017] In this invention, the PA66 is virgin or recycled PA66 resin, and the relative viscosity of the PA66 can be 2.6 to 3.2 (tested under the same conditions). The introduction of PA66 can improve the heat resistance and creep resistance of the composition, complementing PA6, but the compatibility problem between the two needs to be solved.
[0018] In this invention, the epoxy value of the terminally epoxy hyperbranched polyester is 0.3–0.6 mol / 100g, and the number-average molecular weight is 2000–6000 g / mol. Its mechanism of action is as follows: the hyperbranched structure provides numerous reaction sites and free volume. During melt blending, the terminal epoxy groups can undergo ring-opening reactions with the terminal amino and carboxyl groups of recycled PA6 and PA66, forming chemical bonds, thereby generating a hyperbranched-polyamide block copolymer in situ. This copolymer, on the one hand, acts as a macromolecular compatibilizer, significantly improving the interfacial tension between the PA6 and PA66 phases and refining the phase domains; on the other hand, its hyperbranched structure can induce the formation of a partially cross-linked "micro-crosslinked" network, which can effectively disperse and passivate the stress at the crack tip, thereby greatly delaying the propagation of slow cracks.
[0019] Preferably, the terminal epoxy hyperbranched polyester is synthesized using pentaerythritol as the core and dimethylolpropionic acid as the branching unit, with a branching degree of 0.6–0.9, and the terminal hydroxyl groups are modified with epichlorohydrin to obtain an epoxy-capped structure. By controlling the branching degree and epoxy value, the reactivity and crosslinking density can be effectively regulated.
[0020] Preferably, a typical synthesis of the terminal epoxy-based hyperbranched polyester is as follows: Pentaerythritol (0.05 mol) and dimethylolpropionic acid (0.45 mol) are placed in a nitrogen-protected reactor, and p-toluenesulfonic acid (catalyst, 0.5% of the total monomer mass) is added. The mixture is stirred at 140–160 °C under nitrogen protection for 4–6 hours until the acid value is below 5 mg KOH / g, yielding a hyperbranched polyester (theoretical branching degree 0.75). Then, epichlorohydrin (molar ratio to terminal hydroxyl groups 1.2:1) is added, and the mixture is reacted at 60–80 °C in the presence of an alkaline catalyst (triethylamine, 1% of the epichlorohydrin mass) for 6–8 hours. After purification, the terminal epoxy-based hyperbranched polyester is obtained. The branching degree is measured using 1H NMR spectroscopy (1H NMR spectroscopy). 1 The determination was performed by ¹H NMR, using deuterated dimethyl sulfoxide (DMSO-d6) as the solvent. The ratio of branched units to linear units was calculated based on the integrated peak area. The degree of branching was calculated as (number of dendritic units + number of semi-dendritic units) / (number of dendritic units + number of semi-dendritic units + number of linear units).
[0021] In this invention, the nano-whisker nucleating agent is one or more of calcium sulfate whiskers, calcium carbonate whiskers, potassium titanate whiskers, and zinc oxide whiskers, with a diameter of 10–100 nm and an aspect ratio of 10–50. The nano-whiskers not only act as nucleating agents to increase the crystallization temperature and crystallinity of PA6 / PA66 blends and refine spherulite size, but more importantly, they possess a high aspect ratio fibrous structure. During subsequent pipe extrusion molding, by controlling the melt stretch ratio and cooling rate, the whiskers can be induced to orient themselves circumferentially along the pipe, forming a "circumferential barrier structure." This structure is similar to a "ring anchoring" effect, effectively hindering crack propagation along the radial or axial direction of the pipe wall, significantly improving the pipe's resistance to hydrostatic damage.
[0022] Preferably, the nanowhisker nucleating agent is surface-modified with a silane coupling agent, wherein the modification loading of the silane coupling agent is 0.5-2.0% of the total mass of the nanowhisker nucleating agent, and the silane coupling agent is an amino- or epoxy-based silane coupling agent. The surface-modified whiskers exhibit enhanced interfacial bonding with the polyamide matrix, which is beneficial for stress transfer and induced orientation. The surface modification of the nanowhiskers employs a dry modification process: the nanowhiskers are placed in a high-speed mixer and preheated at 100-120°C for 15-30 minutes; the silane coupling agent (0.5-2.0% of the nanowhisker mass) is added via spray, and mixing continues for 15-30 minutes to obtain the surface-modified nanowhisker nucleating agent.
[0023] In this invention, the rare earth metal stearate is one or more of lanthanum stearate, cerium stearate, and yttrium stearate. It plays a crucial multifunctional synergistic role in this invention: First, as a heat stabilizer, it can synergistically inhibit the thermal degradation of recycled PA6 during high-temperature processing with terminal epoxy-based hyperbranched polyesters; second, the unique coordination effect of rare earth elements can form coordination bonds with amide groups on the polyamide molecular chain, acting as physical crosslinking points, further enhancing the interaction force between molecular chains, inhibiting viscoelastic deformation, thereby helping to maintain the orientation structure and improve anti-SCG performance.
[0024] In this invention, the antioxidant is a blend of hindered phenolic antioxidant and phosphite antioxidant, with a mass ratio of (1-3):1, for example, a blend of antioxidant 1098 and antioxidant 168. The lubricant is selected from one or more of calcium stearate, zinc stearate, and ethylene bis-stearamide (EBS) to improve processing fluidity and mold release properties.
[0025] Secondly, the present invention provides a method for preparing a nylon blend pipe composition resistant to slow crack growth, comprising the following steps:
[0026] (1) Drying treatment: Chemically regenerated PA6 and PA66 are subjected to vacuum drying treatment. The vacuum drying temperature is 80-120℃ and the drying time is 4-8 hours until the moisture content of the raw materials is less than 0.05% (by weight).
[0027] (2) Premixing: The dried chemically regenerated PA6, PA66, nano-whisker nucleating agent, rare earth metal stearate, antioxidant and lubricant are put into a high-speed mixer and stirred and mixed for 5 to 15 minutes at 50 to 80°C to obtain a uniform premixed material.
[0028] (3) Segmented melt blending: The premixed material is fed into the main feed port of the twin-screw extruder, and the end-epoxy hyperbranched polyester is fed separately into the side feed port of the twin-screw extruder through a loss-in-weight feeder. The side feed port is located at the position of 1 / 3 to 1 / 2 of the total screw length from the feed end. The melt blending is performed at 240-280°C and a screw speed of 200-400 rpm. The side feeding method can avoid the premature participation of the end-epoxy hyperbranched polyester in the reaction, which may lead to local gelation or excessive crosslinking. Introducing it into the molten polymer matrix can make it uniformly dispersed and effectively participate in reactive compatibilization.
[0029] (4) Granulation: The extruded molten material is granulated by water cooling strip cutting or underwater cutting to obtain nylon blend pipe composition granules.
[0030] The nylon blend pipe composition for resisting slow crack growth described in this invention can be in a molten state or in a solid particle state. The former is obtained by the above step (3), and the latter is obtained by the above step (4). That is, the pipe can be locally formed after step (3), or the pipe can be formed in a different location after step (4).
[0031] Preferably, the twin-screw extruder used in the above preparation process has a length-to-diameter ratio of (36–52):1; the screw assembly includes a combination structure of shearing engagement blocks and reverse screw elements to provide sufficient dispersion and distribution mixing, controlling the average residence time of the material in the barrel to be 1–3 minutes. Too short a residence time results in insufficient reaction, while too long a residence time may lead to thermal degradation or excessive cross-linking.
[0032] In this invention, the addition of rare earth metal stearate to the matrix resin during the premixing stage facilitates its uniform dispersion throughout the system in the early melting stage. In the first half of the twin-screw extruder, it primarily acts as a heat stabilizer, inhibiting early thermal degradation of recycled PA6. After the terminal epoxy-based hyperbranched polyester added at the side feed port reacts to generate a micro-crosslinked network, the rare earth elements in the rare earth metal stearate can coordinate and crosslink with this network and the amide groups on the polyamide chain, forming a second stabilizing structure. These two elements create a stepwise synergistic effect in time and space, thereby maximizing the anti-SCG performance.
[0033] Thirdly, this invention provides a pipe, which is prepared by extrusion molding of the composition prepared by the aforementioned method. During the pipe extrusion molding process, the melt stretch ratio needs to be controlled at 1.5–3.0, and the die cooling rate ≥30°C / min (the die cooling rate refers to the average cooling rate of the outer wall surface of the pipe within the first 30 seconds at a position 10mm after leaving the die, measured using an infrared thermometer). Under these conditions, the molten material is subjected to traction stretching and rapid cooling after leaving the die, causing the nanocrystalline whisker nucleating agent to oriented circumferentially inside the pipe, forming the aforementioned "circumferential barrier structure." Simultaneously, rapid cooling can freeze the molecular chain orientation and whisker orientation, inhibiting their relaxation, thereby effectively locking the orientation structure and maximizing the anti-SCG effect.
[0034] Fourthly, the present invention also provides applications for the aforementioned pipe material, namely: using the pipe material for water supply and drainage pipelines or cryogenic chemical fluid transportation pipelines at temperatures not exceeding 80°C. In these application scenarios, this nylon blend pipe material of the present invention can withstand hydrostatic pressure and fluid medium erosion for extended periods. Due to its excellent resistance to slow crack growth, it can significantly extend its service life and improve safety in use.
[0035] The beneficial effects of this invention are as follows:
[0036] (1) The present invention significantly improves the SCG resistance of the pipe product by blending recycled PA6 with PA66 with specific end group content, and under the action of multiple mechanisms such as compatibilization / micro-crosslinking of end epoxy hyperbranched polyester, orientation enhancement of nano whiskers, synergistic stabilization of rare earth stearate, and control of melt stretch ratio and cooling rate during pipe forming process.
[0037] (2) While improving the SCG resistance of nylon blended pipes, the present invention maintains high tensile strength, flexural modulus and heat distortion temperature, effectively balancing mechanical and thermal properties, and has excellent comprehensive performance.
[0038] (3) The present invention has excellent processing adaptability. Its formulation system is compatible with general twin-screw blending and pipe extrusion processes. The target microstructure can be stably achieved by limiting the process parameters, making it suitable for industrial production.
[0039] (4) This invention realizes the high-value reuse of PA6 through chemical recycling, reduces raw material costs, and has significant environmental and economic benefits, meeting the requirements of green manufacturing. Detailed Implementation
[0040] To make the technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be described in detail below with reference to specific embodiments. However, it should be understood that these embodiments are merely exemplary and do not constitute any limitation on the scope of the present invention. Those skilled in the art can make various modifications and equivalent substitutions to the technical solutions of the present invention without departing from the spirit and scope of the present invention. Moreover, unless otherwise specified, the methods used in the following embodiments are all conventional methods, and the reagents used can be obtained from self-made or commercial sources.
[0041] Example 1
[0042] Example 1 provides a nylon blend pipe composition resistant to slow crack growth, comprising, by weight: 55 parts of chemically recycled PA6 (relative viscosity 2.7, terminal amino content 45 mmol / kg, terminal carboxyl content 60 mmol / kg); 20 parts of PA66 (virgin resin, relative viscosity 2.8); 2.5 parts of epoxy-terminated hyperbranched polyester (epoxy value 0.45 mol / 100g, number average molecular weight 4000, with pentaerythritol as the core, degree of branching 0.75); 1.5 parts of calcium sulfate whiskers (diameter 50 nm, aspect ratio 30, modified with γ-aminopropyltriethoxysilane, loading 1.0%); 0.15 parts of lanthanum stearate; 0.5 parts of antioxidant (hindered phenolic antioxidant 1098 and phosphite antioxidant 168 compounded in a 2:1 ratio); and 0.5 parts of lubricant (ethylene bis-stearamide).
[0043] The preparation method is as follows:
[0044] (1) Drying: Chemically regenerated PA6 and PA66 were vacuum dried at 100°C for 6 hours until the moisture content was <0.05%.
[0045] (2) Premixing: Add the dried PA6, PA66, calcium sulfate whiskers, lanthanum stearate, antioxidant and lubricant to a high-speed mixer and stir and mix at 65°C for 10 minutes.
[0046] (3) Melt blending: The premix is fed into a twin-screw extruder with a length-to-diameter ratio of 44:1 via the main feed. The end-epoxy hyperbranched polyester is fed through a side feed port located at approximately 2 / 5 to 1 / 2 of the screw length. The temperatures of each zone of the extruder are set as follows: 245℃, 255℃, 265℃, 265℃, and 260℃, with a screw speed of 300 rpm. The screw elements include a shear block and a reverse thread element, and the average residence time is controlled to be approximately 2 minutes.
[0047] (4) Granulation: The extruded strip is cooled with water and granulated to obtain the composition granules.
[0048] Examples 2-4
[0049] The composition formulations and some process parameters of Examples 2-4 are shown in Table 1. Components not listed and preparation steps are the same as in Example 1.
[0050] Table 1 shows the formulations and some process parameters for Examples 2-4.
[0051]
[0052] Comparative Example 1
[0053] The difference from Example 1 is that no terminal epoxy hyperbranched polyester is added, while the other components and preparation methods are the same.
[0054] Comparative Example 2
[0055] The difference from Example 1 is that an equal part by weight of unmodified nano-calcium carbonate (particle size of about 100 nm, non-whisker-like) is used instead of calcium sulfate whiskers, while the other components and preparation methods are the same.
[0056] Comparative Example 3
[0057] The difference from Example 1 is that rare earth metal stearate is not added, while the other components and preparation methods are the same.
[0058] Comparative Example 4
[0059] The difference from Example 1 is that the melt stretching ratio during the pipe extrusion molding process is controlled at 1.0, and the die cooling rate is controlled at 35°C / min (still meeting the requirement of ≥30°C / min). The remaining components and preparation methods are the same.
[0060] Comparative Example 5
[0061] The difference from Example 1 is that the melt stretching ratio during the pipe extrusion molding process is controlled at 2.0, and the die cooling rate is controlled at 20°C / min (lower than the 30°C / min limit of this invention). The remaining components and preparation methods are the same.
[0062] Comparative Example 6
[0063] The difference from Example 1 is that the amount of terminal epoxy hyperbranched polyester in the composition is 6 parts, the amount of nano-whisker nucleating agent (i.e., calcium sulfate whiskers) is 4 parts, the amount of rare earth metal stearate (i.e., lanthanum stearate) is 0.4 parts, the amount of antioxidant is 1.5 parts, the amount of lubricant is 1.5 parts, and the remaining components and preparation methods are the same.
[0064] The granules of the compositions obtained in Examples 1-4 and Comparative Examples 1-6 were extruded under the same conditions into nylon blend pipes with a nominal outer diameter of 32 mm and a nominal wall thickness of 3.0 mm (melt draw ratio of 2.0 and die cooling rate of 35°C / min for Examples 1-4 and Comparative Examples 1-3 and 6; melt draw ratio of 1.0 and die cooling rate of 35°C / min for Comparative Example 4; melt draw ratio of 2.0 and die cooling rate of 20°C / min for Comparative Example 5). The following performance tests were performed on the pipes:
[0065] (1) Slow Crack Growth (SCG) Performance: Based on the principle of constant hydrostatic loading in ISO 13479:2022. Specifically: Four axial cuts with a depth of 15% of the pipe wall thickness were prepared on the outer wall of the pipe. Then, the pipe was filled with water in an 80°C water bath and circumferential stress was applied (calculated based on the pipe's SDR value, with an initial circumferential stress of 4.0 MPa). The time to brittle failure of the pipe was recorded. The longer the time, the better the SCG resistance.
[0066] (2) Long-term thermal stability: The evaluation is based on the retention rate of oxidation induction time (OIT, according to ISO 11357-6:2025, test temperature 200℃) before and after aging in a 150℃ thermal aging chamber. The aging time is 1000 hours.
[0067] (3) Mechanical properties: The longitudinal tensile strength and elongation at break of the pipe were tested in accordance with ISO 527-1:2019 and ISO 527-2:2025 standards.
[0068] Table 2 Performance Test Results
[0069]
[0070] As shown in Table 2, the test data of Examples 1-4 of this invention exhibit significantly better SCG resistance than Comparative Examples 1-3. Comparative Example 1 lacks terminal epoxy-based hyperbranched polyester, which cannot effectively repair the molecular chain defects of recycled PA6 and compatibilize the PA6 / PA66 system, resulting in weak interfacial bonding, rapid crack propagation, and an extremely short SCG time. Simultaneously, its mechanical properties and thermal stability also significantly decrease. Comparative Example 2 uses an amorphous whisker-like nucleating agent, which cannot form an effective circumferential barrier structure; therefore, its improvement in SCG resistance is far less than that of the examples. Comparative Example 3 suffers from poor thermal stability and a significantly reduced OIT retention rate due to the lack of rare earth metal stearate, thus demonstrating that rare earth metal stearate plays a crucial role in synergistic antioxidant and system stabilization.
[0071] In Comparative Example 4, the stretching ratio was reduced to 1.0 (below the lower limit of 1.5 specified in this invention). Even with a cooling rate of 35°C / min, the insufficient stretching ratio significantly reduced the circumferential orientation of the nanocrystals, preventing the formation of an effective "circumferential barrier structure." This resulted in a decrease in the SCG failure time to 950 hours, approximately 30% lower than Example 1 (1350 hours). Simultaneously, tensile strength and elongation at break also significantly deteriorated. In Comparative Example 5, the cooling rate was reduced to 20°C / min (below the lower limit of 30°C / min). Even with a stretching ratio maintained at 2.0, the slow cooling caused stress relaxation in the molecular chains and whiskers during cooling, partially destroying the orientation structure. The SCG failure time further decreased to 920 hours, also significantly lower than Example 1. These results clearly demonstrate that only by simultaneously satisfying a melt stretching ratio ≥1.5 and a cooling rate ≥30°C / min can the orientation structure be effectively locked, achieving the expected SCG resistance enhancement effect.
[0072] Furthermore, all functional additives (HBPE, whiskers, rare earth elements, antioxidants, and lubricants) in Comparative Example 6 exceeded the upper limits of the parameters defined in this invention. Although the SCG degradation time (1080 hours) was still better than that of Comparative Examples 1-3, it was significantly lower than that of Example 1 (1350 hours). Tensile strength, elongation at break, and OIT retention all showed a significant decline, especially the elongation at break, which decreased from 210% to 140%, indicating that excessive crosslinking and thermal degradation led to material embrittlement. This demonstrates that more additives are not necessarily better; exceeding the limits defined in this invention will disrupt the system balance, resulting in adverse consequences such as excessive crosslinking, plasticizer precipitation, or thermal stability failure. Comparative Example 6 proves the rationality of the upper limits of each component in this invention and reflects the non-monotonic characteristic of performance changes with dosage.
[0073] As can be seen from the above description, compared with the prior art, after adopting the technical solution of the present invention, through the screening of specific end group content range of recycled PA6, the compatibilization and chain extension effect of end epoxy hyperbranched polyester, the orientation induction of nano whisker nucleating agent and the thermal stability synergistic effect of rare earth metal stearate, combined with specific preparation and molding processes, the final pipe material has excellent long-term hydrostatic resistance and resistance to slow crack growth.
[0074] In summary, the synergistic effect of the components in this invention comprehensively enhances the pipe's resistance to slow crack growth, long-term thermal stability, and mechanical properties, enabling it to meet the stringent requirements of water supply and drainage and low-temperature chemical fluid transportation at temperatures not exceeding 80°C. The composition and preparation method provided by this invention effectively realize the high-value reuse of chemically recycled PA6. The resulting pipe exhibits excellent performance and can be directly applied to existing pipeline production equipment without major modifications, demonstrating industrial practical value and market potential.
[0075] The technical solution, working process, and implementation effects of the present invention have been described in detail above. It should be noted that the described examples are only typical examples of the present invention. In addition, the present invention may have many other specific implementation methods. All technical solutions formed by equivalent substitution or equivalent transformation fall within the scope of protection claimed by the present invention.
Claims
1. A nylon blend pipe composition resistant to slow crack growth, characterized in that, The product comprises the following components by weight: 40-70 parts of chemically recycled PA6, 10-30 parts of PA66, 0.5-5 parts of terminal epoxy hyperbranched polyester, 0.1-3 parts of nano-whisker nucleating agent, 0.05-0.3 parts of rare earth metal stearate, 0.1-1 parts of antioxidant, and 0.1-1 parts of lubricant. The chemically regenerated PA6 is a regenerated PA6 prepared through depolymerization and repolymerization or dissolution and reprecipitation processes. Under the test conditions of 96% concentrated sulfuric acid, concentration 0.5 g / dL, and 25°C, its relative viscosity is 2.4–3.0, terminal amino content is 30–60 mmol / kg, and terminal carboxyl content is 40–80 mmol / kg. The epoxy value of the terminal epoxy hyperbranched polyester is 0.3–0.6 mol / 100g, and the number average molecular weight is 2000–6000 g / mol. The nanocrystal nucleating agent is one or more of calcium sulfate whiskers, calcium carbonate whiskers, potassium titanate whiskers, and zinc oxide whiskers, with a diameter of 10–100 nm and an aspect ratio of 10–50.
2. The nylon blend pipe composition resistant to slow crack growth according to claim 1, characterized in that: The terminal epoxy hyperbranched polyester is synthesized using pentaerythritol as the core and dimethylolpropionic acid as the branching unit, with a branching degree of 0.6 to 0.9, and the terminal hydroxyl groups are modified with epichlorohydrin to obtain an epoxy-terminated hyperbranched polyester.
3. The nylon blend pipe composition resistant to slow crack growth according to claim 1, characterized in that: The rare earth metal stearate is one or more of lanthanum stearate, cerium stearate, and yttrium stearate.
4. The nylon blend tubing composition resistant to slow crack growth according to claim 1, characterized in that: The nano-whisker nucleating agent is surface modified with a silane coupling agent, wherein the modification loading of the silane coupling agent is 0.5 to 2.0% of the total mass of the nano-whisker nucleating agent, and the silane coupling agent is an amino-based or epoxy-based silane coupling agent.
5. The nylon blend pipe composition resistant to slow crack growth according to claim 1, characterized in that: The antioxidant is a mixture of hindered phenolic antioxidant and phosphite antioxidant, with a mass ratio of (1-3):1; the lubricant is selected from one or more of calcium stearate, zinc stearate, and ethylene bis-stearamide.
6. A method for preparing the nylon blend tubular composition resistant to slow crack growth according to any one of claims 1-5, characterized in that, Includes the following steps: (1) Drying treatment: Chemically regenerated PA6 and PA66 are subjected to vacuum drying treatment at a temperature of 80-120℃ for 4-8 hours until the moisture content of the raw materials is less than 0.05%; (2) Premixing: The dried chemically regenerated PA6, PA66, nano-whisker nucleating agent, rare earth metal stearate, antioxidant and lubricant are put into a high-speed mixer and stirred and mixed for 5 to 15 minutes at 50 to 80°C to obtain a uniform premixed material. (3) Segmented melt blending: The premixed material is fed into the main feed port of the twin-screw extruder, and the end-epoxy hyperbranched polyester is fed separately into the side feed port of the twin-screw extruder. The side feed port is located at the position of the barrel corresponding to 1 / 3 to 1 / 2 of the total length of the screw from the feed end. The material is melt blended and extruded at 240 to 280°C and screw speed of 200 to 400 rpm to obtain a molten nylon blended pipe composition. (4) Granulation: The molten material after extrusion in step (3) is granulated by water cooling strip cutting or underwater cutting to obtain a granular nylon blend pipe composition.
7. The method for preparing the nylon blend pipe composition resistant to slow crack growth according to claim 6, characterized in that: The length-to-diameter ratio of the twin-screw extruder is (36-52):1; the screw assembly includes a combination structure of shearing engagement block and reverse thread element, controlling the average residence time of material in the barrel to be 1-3 minutes.
8. A type of pipe, characterized in that: The composition prepared by the method of claim 6 or 7 is prepared by pipe extrusion molding; during the pipe extrusion molding process, the melt stretch ratio is 1.5 to 3.0 and the die cooling rate is ≥30°C / min, so that the nano-whisker nucleating agent in the composition is oriented circumferentially inside the pipe to form a circumferential barrier structure.
9. The use of the pipe according to claim 8, characterized in that: This pipe is used for water supply and drainage pipelines or low-temperature chemical fluid transportation pipelines with a temperature not exceeding 80°C.
Citation Information
Patent Citations
Nylon heat insulation strip material or reinforced nylon and glass fiber reinforced PA6 / PA66 composite material
CN113637193A